EFEKTIFITAS KINERJA BAWASLU DILUAR TAHAPAN PEMILU POTRET BAWASLU KABUPATEN DHARMASRAYA PROVINSI SUMATERA BARAT - rado, alde (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2022)
The purpose of this study was to determine the perspective of regulation on the performance of the Bawaslu of Dharmasraya Regency outside the General Election or Regional Head Election stages and the planning, implementation and performance achievements of the Dharmasraya Regency Bawaslu outside the General Elections or Regional Head Election stages. The method used in this study is a qualitative descriptive method, the author describes all data elements obtained from data sources, monitoring data, data on handling violations and activities carried out by Bawaslu of Dharmasraya Regency outside the stages, data sources are also obtained through interviews, observation and documentation. Based on the available data, it was found that the Dharmasraya Regency Bawaslu carried out the development of participatory supervision, made legal products, strengthened the capacity of human resources, and managed goods suspected of violations.